2008
DOI: 10.1016/j.pec.2008.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Social support as a predictor of perceived health status in patients with multiple sclerosis

Abstract: Social support as a predictor of perceived health status in patients with multiple sclerosis Krokavcova, Martina; van Dijk, Jitse P.; Nagyova, Iveta; Rosenberger, Jaroslav; Gavelova, Miriam; Middel, Berrie; Gdovinova, Zuzana; Groothoff, Johan W. Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
78
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(82 citation statements)
references
References 33 publications
2
78
0
2
Order By: Relevance
“…Similarly, in a study by Krokavcova et al, 48 increasing age was a significant predictor of worse perceived physical health status. Conversely, DiLorenzo et al 49 concluded that the process of getting older enhances perceived mental health in MS.…”
Section: Discussionmentioning
confidence: 65%
“…Similarly, in a study by Krokavcova et al, 48 increasing age was a significant predictor of worse perceived physical health status. Conversely, DiLorenzo et al 49 concluded that the process of getting older enhances perceived mental health in MS.…”
Section: Discussionmentioning
confidence: 65%
“…Sharing experiential knowledge with others in a similar situation provides group members with strategies for coping more effectively with the stresses imposed by MS. Social support plays an important role throughout the course of MS; not only does it empower people to become more independent, but it also gives them the opportunity to depend on loved ones when necessary. Several studies have identified social support as a predictor of perceived health status, both physical and mental, through its stress-mediating and stress-buffering role (Krokavcova et al, 2008;Mohr, Classen, & Barrera, 2004;Schwartz & Frohner, 2005).…”
Section: Social Supportmentioning
confidence: 99%
“…Chan et al showed that the hypothesis that perceived social support can positively influence the physical, psychologic, and social situation and obviously enhances the performance of the individual (10). According to the study by Krokavcova et al and Dennison et al social support can be increase adaptation in people with MS (13,14). Hadavand Khani et al suggested a positive correlation between the hardiness, social support, and mental health.…”
Section: Discussionmentioning
confidence: 98%